Hubungan frekuensi belajar dengan kemampuan matematis siswa - Helma Mustika; Gundala Asri; Sukiyanto Sukiyanto (Journal of Didactic Mathematics, 2022)
This research is motivated by the student's interest in learning in developing the potential for mathematical understanding which is still low. The purpose of this study was to determine the relationship between learning frequency and students' mathematical abilities. This study uses a survey research design with a descriptive correlational method. The data in this study are the results of a study of documentation and questionnaires conducted on students in mathematics. Based on the results of the correlation hypothesis test, the relationship was 36.7%. It can be concluded that the frequency of learning with the mathematical ability of class X science students has a positive weak correlation. This means that there is a relationship between the frequency of learning with the mathematical ability of class X science students. Where if the frequency of student learning is high, the higher the student's mathematical ability.